Upaya Peningkatan Pengetahuan Ibu Balita Terkait MP ASI Kaya Protein Hewani di Posyandu di Wilayah Kerja Puskesmas Hajimena - Afiska Prima Dewi; Ritma Dewanti; Syamsopyan Syamsopyan; Suherman Suherman; Hernianti Hernianti (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Stunted is a growth disorder in children due to chronic malnutrition and repeated infections. Stunted is characterized by the child's length or height being below the standard identified through anthropometric measurements using the PB/U or TB/U index. One of fulfillment of toddler nutritional is MP ASI (Complementary Food for Breast Milk). MP ASI that rich in animal protein can provide sufficient nutrients for toddlers so that can avoid stunted problems. Therefore, it is necessary to increase the knowledge of toddlers’ mothers regarding MP ASI that rich in animal protein. This event was carried out at 2 Posyandu : Posyandu Induk Desa Pemanggilan and Posyandu Srimulyo I H on February 6 and 7, 2024. Target of this activity was mothers of toddlers at both Posyandu. The results showed an increase in knowledge before and after nutrition education that indicated by the results of Wilcoxon Test : p value of 0.025 (<0.05) on the first day and p value of 0.047 (<0.05) on the second day.